P‐9.5: Homogenous Integration Methods for Micro‐LED and 2T1C Structure HEMT. (4th October 2019) - Li, Silong; Zheng, Jintao; Liu, Zhaojun
Abstract : The display is an essential part of our life, Micro‐LED (Micro‐Light Emitting Diode), as an emerging display technology, competes with OLED (Organic Light Emitting Diode) and QLED (Quantum‐dot Light Emitting Diode) to become the mainstream technology of the next generation of display technology in the display industry. Due to its advantages such as high resolution, high brightness, high response frequency, high stability, low power consumption, Micro‐LED has very big application prospect. GaN‐based HEMT (High Electron Mobility Transistor) also is the research hot point due to its high electron mobility. Due to they are the same material, it is possible to combine two of them. In this paper, a homogenous integration method of HEMT driver circuit of 2T1C (2 transistors and 1 capacitor) structure with micro LEDs is proposed and simulated by Silvaco software.